Microbe‐mineral biogeography from multi‐year incubations in oceanic crust at North Pond, Mid‐Atlantic Ridge. (8th January 2021) - Orcutt, Beth N.; D'Angelo, Timothy; Wheat, C. Geoff; Trembath‐Reichert, Elizabeth
Summary: Subseafloor oceanic crust is a vast yet poorly sampled habitat for life. Recent studies suggest that microbial composition in crustal habitats is variable in space and time, but biogeographic patterns are difficult to determine due to a paucity of data. To address this, we deployed hundreds of mineral colonization experiments at and below the seafloor for 4–6 years at North Pond, a borehole observatory network in cool (<10°C) and oxic oceanic crust on the western flank of the Mid‐Atlantic Ridge. The overall community composition of mineral incubations reveals that colonization patterns are site dependent, with no correlation to mineral type. Only a few members of the Thioalkalispiraceae and Thioprofundaceae exhibited a mineral preference pattern, with generally higher abundance on metal sulphides compared to silicates, while taxa of the Gammaproteobacteria and Deltaproteobacteria were common in the colonization experiments. In comparison to datasets from other crustal habitats, broader biogeographic patterns of crustal communities emerge based on crustal habitat type (surface‐attached communities versus fluid communities), redox environment and possibly crustal age. These comparisons suggest successional biogeography patterning that might be used as an indicator of how recently permeable pathways were established within oceanic crust.